Experiences of deprivation of freedom from the perspective of men and its implications to health care - Francisco Daniel Brito Mendes; Zaira de Andrade Lopes; Alberto Mesaque Martins; Helder de Pádua Lima; Marianna de Francisco Amorim (Universidade Federal do Ceará, 2023)
Objective: to understand the experiences of deprivation of freedom from the perspective of men and their implications to health care. Methods: qualitative study carried out with 10 men serving sentences on probation. Data collection was carried out in individual interviews using a semistructured questionnaire. Data was submitted to content analysis. Results: three categories emerged, which were: Crooked life: living before being deprived of freedom; Caged bird: being a man deprived of freedom; and Time bomb: health care in the prison system. The deprivation of freedom is an experience marked by the lack of safety, considering the health risks in the prison environment, the perception of participants of being vulnerable to disease, and the denial, on the part of the state, of the right to health. Since the access to health is not guaranteed, relatives were the most commonly responsible for organizing care. Conclusion: an unhealthy situation was found, with vulnerability to disease and denial of the right to health in the prison environment. Contributions to practice: this study contributed for sensitizing professionals who work in the prison system, emphasizing the importance of guaranteeing human rights during imprisonment.